Optimizing the Role of Local Government in the Development of Sustainable Tourism - Puput Mulyono; Arditya Prayogi; Aris Prio Agus Santoso; Zaenal Mustofa (SS&H: Studies in Social Sciences and Humanities, 2025)
The rapid recovery of the tourism sector in the post-pandemic era has increased the need for sustainable tourism development at the local level. Local governments have a strategic role in ensuring that tourism growth is able to provide economic benefits while maintaining social and environmental sustainability. However, various empirical evidence shows that the implementation of sustainable tourism policies at the regional level is still uneven and often faces institutional challenges and coordination between stakeholders. This study aims to analyze the role of local governments in encouraging sustainable tourism development and identify strategies for optimizing these roles in the current governance context. This research uses a qualitative descriptive approach with a policy and stakeholder analysis framework. Data was collected through document analysis of regional tourism policies, development plans, and relevant secondary data sources, and analyzed using thematic analysis techniques. The results of the study show that local governments generally play the role of regulators and facilitators, but the effectiveness of these roles is still limited by limited institutional capacity, weak collaboration between stakeholders, and the lack of optimal integration of sustainability principles in operational practices. This research also identifies opportunities to strengthen governance through collaborative planning, community empowerment, and the implementation of adaptive policy instruments. The study contributes to the development of the literature by highlighting the gap between policy formulation and implementation at the regional level and offering an integrative framework for optimizing the role of local governments in sustainable tourism development. The findings of this study provide strategic implications for policymakers in strengthening sustainable tourism governance at the regional level.